Pode uma versão incompatibilista de liberdade fazer sentido? : um estudo a partir de Robert Kane - Pulla, Danusia Braeske (2018)
This dissertation aims to study the problem of free will in the compatibilism x incompatibilism debate from the perspective of Robert Kane. We first seek to characterize these two philosophical views and present their main arguments. In a second moment, we examine two conditions Kane´s takes as necessary for free will, namely alternative possibilities and ultimate responsibility. In the third chapter we explore specifically the theory of Robert Kane, mainly through the analysis of his work The Significance of Free Will. In the last chapter we discuss and comment on some of the main criticisms of the philosopher's theory. Throughout this work we analyze indeterminism from different perspectives in order to better understand the problems that constitute the greatest challenge to the intelligibility of incompatibilist free will. In the end, we conclude that there is still a way to go in order to respond satisfactorily to some criticisms but it seems too early or too strong to claim that Kane's freedom is not coherent or intelligible.